Perilaku Petani Terhadap Adopsi Teknologi M-Bio untuk Pengembangan Usahatani Agroforestri - Rudi Priyadi; Rina Nuryati; Faqihuddin (Bahasa Indonesia, 2022)
Abstract This study aims to determine the behavior of farmers in adopting M-Bio technology for the development of agroforestry farming. The research method is a survey with data collection techniques: observation and in-depth interviews with respondents. Research variables include farmer behavior towards the implementation of counseling and training as well as farmer behavior towards the adoption of M-Bio Technology. The research was conducted in Setiawaras Village in the Cipigan Insan Mandiri and Dadap Sari farmer groups from July to October 2020. The data analysis used was descriptive analysis with a Likert scale with scores of 1, 2, 3, 4, and 5 then measured by weighted values. The data distribution was converted into a ratio scale with a score between 0–100. Furthermore, the scores are grouped into: (1) Very Low: 0–20; (2) Low: 21 - 40; (3) Moderate: 41–60; (4) Height: 61–80; and (5) Very High: 81-100. The results showed that the behavior of farmers towards the implementation of counseling and training on M-Bio technology with all its indicators (presentation and practice, attention, comprehensiveness, results and retention) had a score between 80 - 100 so all of them were categorized as very high. Likewise, the behavior of farmers towards the adoption of M-Bio technology for the development of agroforestry farming along with all its indicators concerning cognitive, apective, and conative aspects has a score between 80 - 100 so that all of them are also categorized as very high. Abstrak Penelitian bertujuan untuk mengetahui perilaku petani dalam adopsi teknologi M-Bio untuk pengembangan usahatani agroforestri. Metode penelitian adalah survey dengan teknik pengumpulan data : observasi dan wawancara mendalam dengan responden. Varibel penelitian mencakup perilaku petani terhadap pelaksanaan penyuluhan dan pelatihan serta perilaku petani terhadap adopsi Teknologi M-Bio. Penelitian dilaksanakan di Desa Setiawaras pada kelompok tani Cipigan Insan Mandiri dan Dadap Sari dari bulan Juli sampai Oktober 2020. Analisis data yang digunakan adalah analisis deskriptif dengan skala likert skor 1, 2, 3, 4, dan 5 kemudian diukur dengan nilai tertimbang. Sebaran data diubah menjadi skala rasio dengan skor antara 0–100. Selanjutnya, skor dikelompokkan menjadi : (1) Sangat Rendah:0–20; (2) Rendah:21 – 40; (3) Sedang:41–60; (4) Tinggi:61–80; dan (5) Sangat Tinggi: 81-100. Hasil penelitian menunjukkan bahwa perilaku petani terhadap pelaksanaan penyuluhan dan pelatihan teknologi M-Bio dengan seluruh indikatornya (presentasi dan praktek, atensi, komprehensif, hasil dan retensi) memiliki skor antara 80 – 100 sehingga semuanya terkategori sangat tinggi. Demikian juga dengan perilaku petani terhadap adopsi teknologi M-Bio untuk pengembangan usahatani agroforestri beserta seluruh indikatornya yang menyangkut aspek kognitif, apektif, dan konatif memiliki skor antara 80 – 100 sehingga semuanya juga terkategori sangat tinggi.